J. A. SCHUMPETER PÓŁ WIEKU PÓŹNIEJ - WSPÓŁCZESNA RECEPCJA TEORII - Maślak, Elżbieta (Wydział Prawa i Administracji UAM, 2002)
The aim of this paper is to present the core concepts of the work of Joseph A. Schumpeter, a person that is considered to be one of the greatest economists of the 20th century. In his numerous works he makes attempts at explaining the methodological concepts related to economics as a science, explore certain social phenomena like democracy, social and institutional change and make predictions about the transformation from capitalism into socialism. However, Schumpeter’s greatest contribution is his explanation of the development o f the capitalist market economy, the factors and process of economic development. Unlike neoclassical economists, J. A. Schumpeter seeks progress factors among endogenous objects, i.e. innovations. Progress initiators are those entrepreneurs who introduce innovations to the market. Schumpeter is therefore regarded to be the founder of the innovation theory. Schumputerian ideas, though slightly forgotten after his death, are again beginning to gather importance similar to those of J. M. Keynes. The growing popularity o f the postschumpeterian (evolutionary) economics centred around the phenomenon of technical change proves that Schumpeter’s theory has not lost its relevance.
J. A. SCHUMPETER HALF A CENTURY LATER - CONTEMPORARY RECEPTION OF THE THEORY